Using Video to Increase Children’s Knowledge About Healthy Food: Strengthening Teacher Teaching Skills - Nur Riska; Indriani, Tari; Nadhifah Irma Rahmahsari (JPUD - Jurnal Pendidikan Usia Dini, 2023)
The teaching skills of teachers at the early childhood education level are essential for the physical, motor, and psychological development stages of children. This research aims to increase children’s knowledge about healthy food through video media to strengthen teachers’ teaching skills. This research uses a qualitative approach with an exploratory type of research. The sample used was 10 early childhood educators. The findings in this research are the impact of using healthy food video media, namely helping children connect previous experiences with newly discovered knowledge. Then, in the core activity, serving healthy food according to recipes and food ingredients that have been watched on healthy food video media can improve students’ psychomotor development and at the end, the teacher asks students about the feelings that arise during learning, which is the teacher’s effort to accompany psychological development as an impact that arises. from learning activities using healthy food video media. Keywords: video healthy foods, early childhood, teaching skills References: 1 Andrini, V. S. (2016). The Effectiveness of Inquiry Learning Method To Enhance Students ’ Learning Outcome : A Theoritical And Empirical Review. 7(3), 38–42. Batubara, H. H., & Ariani, D. N. (2016). Pemanfaatan Video Sebagai Media Pembelajaran Matematika Sd/Mi Informasi Artikel. 2(1), 47–66. Https://Doi.Org/10.31602/Muallimuna.V2i1.741 Elprida, K., Sujana, W., Tirtayani, L. A., Pendidikan, J., Anak, P., Dini, U., Pendidikan Guru, J., & Dasar, S. (2018). Pengaruh Keterampilan Dasar Mengajar Guru Terhadap Perilaku Disiplin Pada Anak Usia Dini Kelompok B (Vol. 6, Issue 1). Fajrin, R., & Ana, R. (2020). Persepsi Siswa Terhadap Keterampilan Mengajar Guru Menggunakan Media Visual (Vol. 4, Issue 2). Hardiyanti, W. E., Ilham, M., Ekadayanti, W., & Jafarudin. (2020). Gorontalo 96128 2 PGMI, Fakultas Tarbiyah Dan Ilmu Pendidikan. Indonesia Jl. Kapt. Piere Tendean, 3(2), 93563. Husein Batubara, H., Noor Ariani, D., & Prodi Penddikan Guru, D. (2016). Pemanfaatan Video Sebagai Media Pembelajaran Matematika Sd/Mi Informasi Artikel. Oktober, 2(1). Juandi, A., & Sontani, U. T. (2017). Keterampilan Dan Kreativitas Mengajar Guru Sebagai Determinan Terhadap Prestasi Belajar Siswa. 2(2), 242–250. Juniyanasari, L. P., Pudjawan, K., & Ujianti, P. R. (2015). Penerapan Pembelajaran Kontekstual Melalui Cooking Class Untuk Meningkatkan Keterampilan Motorik Halus Pada Anak. 3. Https://Doi.Org/10.23887/Paud.V3i1 Kurniawan, T. D. (2016). Pengaruh Penggunaan Media Video Pembelajaran Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial Siswa Kelas V Sd Se-Kecamatan Gedangsari Gunungkidul. 21–26. Https://Doi.Org/10.30738/Trihayu.V3i1.739 Kurniawaty, L. (2017). Peningkatan Pengetahuan Tentang Makanan Sehat Melalui Kegiatan Bermain Cooking Class Jurnal CARE ( Children Advisory Research and Education ) Volume 4 Nomor 2 Januari 2017 Pendahuluan Pertumbuhan Dan Perkembangan Anak Usia Dini Ditentukan Oleh Makanan Yan. 4(3). Mulyawati, Y., & Purnomo, H. (2021). Pentingnya Keterampilan Guru Untuk Menciptakan Pembelajaran Yang Menyenangkan. Https://Doi.Org/10.33654/Pgsd Nurchayati, D., & Pusari, W. P. (2015). Upaya Meningkatkan Pengetahuan Makanan Sehat Melalui Penerapan Sentra. Https://Doi.Org/10.26877/Paudia.V3i2 Oktober.510 Nasirun, ), Suprapti, A., Qalbi, Z., Indrawati, ), & Keguruan, F. (2023). peningkatan profesionalisme guru melalui pelatihan keterampilan mengajar bagi guru paud al-jundi kota bengkulu improving teacher professionalism through teaching skills training for paud teachers al-jundi bengkulu city. 4(1), 17–22. Https://Ejournal.Unib.Ac.Id/Index.Php/Abdipaud/Index Perdani, Z. P., & Hasan, R. (2016). Hubungan Praktik Pemberian Makan Dengan Status Gizi Anak Usia 3- 5 Tahun Di Pos Gizi Desa Tegal Kunir Lor Mauk. August. Https://Doi.Org/10.31000/Jkft.V2i2.59 Pramana, C. (2020). Pembelajaran Pendidikan Anak Usia Dini (PAUD) Dimasa Pandemi Covid-19. Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2(2), 115. Https://Doi.Org/10.35473/Ijec.V2i2.557 Rahman, F. R., Agustina, I. O., Fauziah, I. N., & Saputri, S. A. (2022). Pentingnya Keterampilan Dasar Mengajar Untuk Menjadi Guru Profesional Sekolah Dasar. 4, 13265–13274. Renovia, R., Hartati, S., & Rahayu, W. (2018). Prosiding Seminar Dan Diskusi Nasional Pendidikan Dasar. Sahyan, Rauter, U. H., & Nazlia, I. (2023). Manfaat Rencana Pelaksanaan Pembelajaran Harian (Rpph) Untuk Meningkatkan Kemampuan Guru Dalam Mengajar Anak Usia Dini Di Ra Sulthonul Fadhilah Medan Marelan (Vol. 3, Issue 1). Shofiyah, N., Nisak Aulina, C., & Efendi, N. (2021). Peningkatan Kompetensi Pedagogik Guru PAUD Dalam Pembuatan Video Pembelajaran Sains Berbasis Smartphone. Murhum : Jurnal Pendidikan Anak Usia Dini, 23–33. Https://Doi.Org/10.37985/Murhum.V2i1.29 Suryani, L., & Seto, S. B. (2020). Penerapan Media Audio Visual Untuk Meningkatan Perilaku Cinta Lingkungan Pada Golden Age. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 900–908. Https://Doi.Org/10.31004/Obsesi.V5i1.601 Van De Grift, W. J. C. M., Houtveen, T. A. M., Van Den Hurk, H. T. G., & Terpstra, O. (2019). Measuring Teaching Skills in Elementary Education Using the Rasch Model. School Effectiveness and School Improvement, 30(4), 455–486. Https://Doi.Org/10.1080/09243453.2019.1577743 Wuryanti, U. (2016). Motivation and Character Hard Work on The Fifth Grade. 232–245. Https://Doi.Org/10.21831/Jpk.V6i2.12055